Evaluación de percepción de la calidad de servicio del centro gerontológico Nuevo Amanecer del cantón Chinchipe, provincia de Zamora Chinchipe, 2023. - Cabrera Alvarez, Erica Germania (2024)
The purpose of this research was to measure the perception of the quality of care service for old adults at the Nuevo Amanecer gerontological center. The general objective was established: To evaluate the perception of the quality of service of the Nuevo Amanecer gerontological center of the Chinchipe canton, Province of Zamora Chinchipe, 2023, in the same way, the following specific objectives were established: To describe the current situation, followed by measuring satisfaction of quality and, finally, propose areas of improvement that contribute to optimizing the quality of service for the Nuevo Amanecer gerontological center. To carry out this research, a methodology with a mixed approach was used, an observation sheet was applied to determine the current situation of the center; in addition, a survey was applied through an adaptation of the SERVPERF model with the sole purpose of measuring the quality perception. This questionnaire was evaluated on a total of 40 old adults. Each statement was evaluated using the Likert scale, with a score range from 1 to 5, in this way, the final perception of the service has a value of 4.38 out of 5 points, which becomes a good evaluation, therefore, these dimensions must constantly improve.